Peran BPK sebagai Lembaga Negara dalam Meningkatkan Akuntabilitas Keuangan di Indonesia - Amalyh, Cut Faizal Salsabilah Ni Ajeng; Firnanda, Irma; Merliani Riskiana Putri; Rahmaleni, Wikha; Anffa, Al; Hadji, Kuswan (Judge : Jurnal Hukum, 2025)
The Financial Audit Agency (BPK), which is a state institution, has an important role in maintaining public accountability through auditing the management and responsibility of state finances. Applying the organizational maturity model, the BPK seeks to ensure transparency, compliance and prevent acts of corruption and budget misuse. Quality inspection results become the basis for government entities to improve performance and accountability. Transparency of BPK audit results also contributes to improving public policy. Nevertheless, the BPK faces a number of challenges in carrying out its duties. This abstract will review further the duties, functions, performance, impacts, challenges, as well as comparisons of the BPK with similar institutions in the context of accountability and performance.